Respuesta :
Answer:
3y=3x+ c
Step-by-step explanation:
-3= x1 and 3 = y1
-6= x2 and 2= y2
y2-y1/ x2-x1 = 2-3/ -6+3 = -1/-3 =1/3 (the gradient)
y =1/3x +c
multiplying both sides by 3
3y= 3x +c in the form of y= mx + c
First of all In an equation you need slope and y-intercept according to the rule Y=Mx+c
M= y2-y1/x2-x1 = 2-3/-6-(-3) = -1/-3 = 1/3
Y= 1/3x+c
(NOW WE HAVE THE SLOPE AND WE CAN FIND THE Y-INTERCEPT BY REPLACING IN ONE OF THE GIVING POINTS)
3= 1/3(-3)+c
C=4
Final answer is y = 1/3x + 4
M= y2-y1/x2-x1 = 2-3/-6-(-3) = -1/-3 = 1/3
Y= 1/3x+c
(NOW WE HAVE THE SLOPE AND WE CAN FIND THE Y-INTERCEPT BY REPLACING IN ONE OF THE GIVING POINTS)
3= 1/3(-3)+c
C=4
Final answer is y = 1/3x + 4